Eco-Friendy Project di Desa Kemuning Lor, Kabupaten Jember - Gamasiano Alfiansyah; Selvia Juwita Swari; Ria Chandra Kartika; Mudafiq Riyan Pratama (Journal of Community Development, 2025)
The increasing population is followed by a rise in waste production, both organic and inorganic. A preliminary survey showed that households generate a large amount of organic waste that has not been properly processed. The community tends to dispose of waste at landfills and then burn it. The aim of this activity is to implement the Eco-Friendly Project by converting organic waste into eco-enzyme in Kemuning Lor Village, Jember Regency. The target participants of this community service activity are members of the PKK, health cadres, youth groups, and village officials. The results showed an increase in participants' understanding, and they were able to independently produce eco-enzyme from organic waste. It is recommended that continuous activities be conducted to provide health education to the community, and that the results of this community service activity be disseminated widely to the public.